Seurge- Weber Disease: A case report - Sri Sutarni Sri Sutarni (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1983)
Sturge-Weber Disease is one of the congenital malforMations, in which we find naevus facialis, general or focal convulsion, mental retardation, and contralateral hemiparesis; sometimes also choroid angiomata, buphthalmus and glaucoma.Skull rbntgenology, a E. G. and cerebral angiography make the diagnosis clear.We reported on a boy, 5 years old, with Sturge-Weber Disease who came to the Hospital with convulsion.Key Words: Sturge-Weber Disease - congenital malfOrmation - naevus facialis - convulsion - mental retardation